Cerebrospinal fluid analysis: current diagnostic methods in central nervous system infectious diseases - Gomes, Hélio Rodrigues (Arquivos de Neuro-Psiquiatria, 2022)
Cerebrospinal fluid (CSF) analysis is an important diagnostic tool for many conditions affecting the central nervous system (CNS), especially CNS infectious diseases. Despite its low specificity, CSF white blood cell counts, CSF protein levels, CSF serum glucose ratio and CSF lactate measurement are useful in differentiating infections caused by distinct groups of pathogens. CSF direct examination and cultures can identify causative organisms and antibiotic sensitivities as well. Adjunctive tests such as latex agglutination, different immunological assays and molecular reactions have great specificities and increasing sensitivities. In this article, some recent diagnostic methods applied to CSF analysis for frequent CNS infections are presented.
Keywords: Cerebrospinal Fluid; Central Nervous System Bacterial Infections; Biomarkers; Metagenomics; Neurosyphilis; Meningoencephalitis